Fast screening of gold in rock samples using polyurethane foam extraction and inductively coupled plasma mass spectrometry determination - Jalal Hassan; Naeemeh Zari; Mohammad-Hadi Karbasi (MethodsX, 2025)
In this work, the volume of sample solution and concentration of gold was optimized for extraction with foam in dimensions (1 × 1 × 1) and then was used for extraction from soil samples. The results showed that the proposed technique has a good analytical efficiency compared to the standard fire assay method and the accuracy of work is in the range of 74–125 %. The equation of linear calibration curve was obtained with regression coefficient better than 0.9997, and the detection and quantification limit of the gold in aqueous and soil sample obtained 0.25 and 0.8 µg kg −1, respectively. • This method is inexpensive and fast for determination of gold in various samples. • This method has high thought of sample determination. • This method is green chemistry method.